The role of context in the globalization of Chinese firms - John Child; Svetla Trifonova Marinova (University of Birmingham, Birmingham Business School, 2013)
This paper argues that it is crucial to take account of both home and host country contexts in order adequately to understand their implications for Chinese enterprises investing into foreign countries. This calls for an analysis that is sensitive to both home and host country contexts, and that takes into account how the institutions and political systems in those contexts establish institutional and resource capital needs for the overseas-investing firm. We discuss and illustrate three different conjunctions of Chinese and host country characteristics, and the firm-level learning and adaptation required in the light of the relevant capitals likely to be available to Chinese firms. The analysis draws upon insights from resource-based, institutional and political perspectives. While it is developed with specific reference to China, we also suggest that this form of analysis can be applied more generally to the implementation of outward foreign direct investment from any country.
Keywords: 330; Adaptation; China; Context; Firm; Government; Home country; Host country; Institutional capital; OFDI; Resource capital